2021
DOI: 10.1186/s12940-021-00796-x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory function declines in children with asthma associated with chemical species of fine particulate matter (PM2.5) in Nagasaki, Japan

Abstract: Background The differential effects of PM2.5 fractions on children’s lung function remain inconclusive. This study aimed to examine whether lung function in asthmatic children was associated with increased PM2.5 fractions in urban areas in Nagasaki prefecture, Japan, where the air pollution level is relatively low but influenced by transboundary air pollution. Methods We conducted a multiyear panel study of 73 asthmatic children (boys, 60.3%; mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…We found that personal exposure to air pollutants reduced lung function in single- and two-way air pollutant models. The association between air pollutants and respiratory function has been explored by several studies ( Kim et al, 2021a ; Gehring et al, 2020 ). Although previous studies also explored other respiratory function parameters such as FEV 1 and FVC, and we only explored PEF, our results were akin to most previous findings ( Kim et al, 2021a ), ( Gehring et al, 2020 ), ( Ye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that personal exposure to air pollutants reduced lung function in single- and two-way air pollutant models. The association between air pollutants and respiratory function has been explored by several studies ( Kim et al, 2021a ; Gehring et al, 2020 ). Although previous studies also explored other respiratory function parameters such as FEV 1 and FVC, and we only explored PEF, our results were akin to most previous findings ( Kim et al, 2021a ), ( Gehring et al, 2020 ), ( Ye et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The association between air pollutants and respiratory function has been explored by several studies ( Kim et al, 2021a ; Gehring et al, 2020 ). Although previous studies also explored other respiratory function parameters such as FEV 1 and FVC, and we only explored PEF, our results were akin to most previous findings ( Kim et al, 2021a ), ( Gehring et al, 2020 ), ( Ye et al, 2021 ). Such findings may be explained by the oxidative stress produced after exposure to pollutants, which may lead to airway hyper-reactivity and lung injury ( Ghio et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nagasaki air pollution is relatively low but is influenced by transboundary air pollution from Asia and Eurasia 28 , 33 , 34 . Studies conducted in Nagasaki have demonstrated that air pollution has adverse health effects, especially in children 14 , 16 . Moreover, 8.3 and 29.6% of the population in Nagasaki Prefecture are less than or equal to 10 and more than or equal to 65 years of age, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, rarely studies have combined these to generate a more holistic understanding that can help identify health risk areas, influencing factors, pollution trends, and the efficacy (or lack thereof) of policy interventions 11 . For instance, in Nagasaki Prefecture, most of the studies have only focused on either the health impact caused by air pollutants [14][15][16] , the long-range transport of air pollutants from the Asian continent [17][18][19] , or the effects of climatic variables and the spatial and temporal distribution of PM 2.5 20 . Although these studies provide essential information, a multi-method approach is necessary to understand better the distribution, factors, and current and future trends of PM 2.5 and NO 2 pollution in Nagasaki Prefecture.This study used a multi-method approach to analyze PM 2.5 and NO 2 data in Nagasaki Prefecture from 2013 to 2021.…”
mentioning
confidence: 99%